The Issue Management Of Village Government In Managing Cash Direct Assistance Program In Taba Mutung Village Of Karang Tinggi District Of Central Bengkulu Regency - Meli Harni; Narti, Sri; Indria (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to determine the management of village government issues in managing the direct cash assistance program in Taba Mutung Village, Karang Tinggi District, Central Bengkulu Regency as input for the Taba Mutung Village Government's strategy in responding to future problems. Direct Village Cash Assistance (BLT-Desa) is cash assistance to poor families in villages sourced from the Village Fund to reduce the impact of the COVID-19 pandemic. The research method used is qualitative description. Data collection techniques use observation, interviews and documentation methods. The analysis techniques used are data reduction, data presentation and drawing conclusions. The research results show that (1) Village government issue management by identifying issues, namely investigating and tracing issues related to direct cash assistance (BLT) problems that are developing in the community for follow-up. (2) Village government issue management by means of issue analysis, namely finding issues that are important to resolve so that the issue does not spread widely. (3) Issue management by selecting an issue strategy, namely by inviting people whose names have been excluded from the list of recipients of direct cash assistance (BLT) to held internal meetings. (4) Village government issue management with an issue handling program, namely with mutually agreed policies, namely the distribution of basic necessities to people who are excluded from direct cash assistance (BLT) recipients and those affected by Covid-19. (5) Village government issue management with evaluation of results, namely To anticipate issues that will develop in the community, the village government provides direction and explanation to the community first before taking or determining a decision, so that a decision that will be made does not cause issues in the community because they have not received a direct explanation related to a decision or decree.